REDESAIN DAN OPTIMALISASI BALAI RUKUN WARGA (RW) SEBAGAI EPISENTRUM AKTIVITAS DAN PEMBERDAYAAN KOMUNITAS LOKAL - Bagus Suryanto; Ahmad Khoiri; Kurniawati Mutmainah; Nurma Khusna Khanifa (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The optimization of public infrastructure is a fundamental pillar of community service aimed at addressing the socio-spatial needs of urban residents. The Rukun Warga (RW) hall in Kampung Pongangan RT 03 RW 12, Wates Village, Magelang City possesses significant latent potential to be transformed into an integrated community hub. This participatory community service project was collaboratively executed by lecturers and students through a systematic framework involving local government coordination, field site surveys, structural measurements of the existing layout, and advanced architectural drafting using computer-aided design (CAD) software. The definitive outputs encompass comprehensive architectural documents, including detailed floor plans, multi-perspective elevations (front, side, and rear views), and high-fidelity three-dimensional renderings. The proposed spatial configuration emphasizes a hybrid functionality, positioning the RW hall not only as a formal administrative meeting space but also as an inclusive arena for social cohesion, non-formal education, cultural preservation, and grassroots economic acceleration. The visual blueprints received highly favorable validation from village executives and community representatives, establishing a robust framework for execution towards a more productive, adaptive, and sustainable public facility.